Peranan Manajemen Sekuriti Terhadap Keamanan Cyber Bersumber Nilai-Nilai Kebangsaan UUD 1945 Dalam Meningkatkan Efektivitas di Era Digitalisasi Untuk Keamanan Nasional - Destya Fitri Andini; Edy Soesanto; Lusiana Prastiwi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the constantly advancing era of digitalisation, ensuring cyber security has become essential in preserving the integrity, confidentiality, and accessibility of organisational data. The primary focus of this research is to emphasise the importance of cybersecurity awareness in safeguarding systems and information. The 1945 Constitution serves as the primary governing document for the government and legal system. The 1945 Constitution enacts legislation that ensures freedom of expression, a pertinent principle in cyber security. This research aimed to examine the role of security management in enhancing cyber security by applying principles in accordance with the 1945 Constitution. This research identified the factors affecting cyber security awareness and proposed strategies to enhance user awareness through a comprehensive literature review and examined recent findings. Security management is essential for guaranteeing the security of IT systems and infrastructure. Based on a literature review, this study determined the role of security management in assisting organisations in identifying, managing, and addressing security threats effectively. In addition, the hypothesised findings concluded that advancing cyber security in Indonesia is a fundamental aspect of state sovereignty, as stated in the 1945 Constitution and the principle of the Unitary State of the Republic of Indonesia (NKRI). These findings demonstrated the significance of comprehending cyber security for users and organisations and the necessity of international cooperation in the realm of national security in cyber. By gaining a more comprehensive comprehension of the function of security management, it is anticipated that organisations can enhance security protocols and mitigate security vulnerabilities as they confront the challenges of the present digital age.